2011
DOI: 10.2355/isijinternational.51.544
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorization Treatment of High Phosphorus Iron Ore by Pre-reduction, Air Jet Milling and Screening Methods

Abstract: This paper proposes a novel process for the pre-treatment of high phosphorus iron ore by pre-reduction, air jet milling and screening methods. The dephosphorization behavior was evaluated as a function of such parameters as the milling gas kinetic energy, Ek and specific energy consumption, Esp. At a fixed milling gas kinetic energy, the dephosphorization treatment behavior was highly dependent on the solids feed rate and the degree of sintering of the pre-reduced phases. The proposed pre-treatment process inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The reduction process was proved to be beneficial for iron recovery though, the authors found that it is very difficult to separate the ferrous phase with the P-containing gangue, this phenomenon was also found in other researchers' work. 13,14) Besides, most of the P exists in the form of inter-grew structure with hematite hampering the mechanical separation. It seems that the smelting process is necessary in order to separate the P from the Fe.…”
Section: Comparison With Other De-p Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction process was proved to be beneficial for iron recovery though, the authors found that it is very difficult to separate the ferrous phase with the P-containing gangue, this phenomenon was also found in other researchers' work. 13,14) Besides, most of the P exists in the form of inter-grew structure with hematite hampering the mechanical separation. It seems that the smelting process is necessary in order to separate the P from the Fe.…”
Section: Comparison With Other De-p Methodsmentioning
confidence: 99%
“…MATINDE et al also found the contradictory relation and pointed out the difficulty of P-Fe separation due to the phenomenon that powdery gangue surrounded reduced iron. 14) From this point of view, a integrated process combines pre-reduction (solid state) and mechanical separation methods could not separate the Fe and Pcontaining phases efficiently.…”
Section: Characterization Of Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, lower the reduction temperature is beneficial for the dephosphorization during the coal-based reduction process, while it will hinder the reduction rate of the reduced product. Therefore, E. Matinde, 16,17) S. J. Bai 18) and W. Yu 19) have widely investigated the function of dephosphorization by adding Ca(OH) 2 and Na 2 CO 3 on the coal-based reduction, the experiment results show that the additives is beneficial for the dephosphorization during the ore-carbon reduction in a semi-molten state.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the abundant high phosphorus oolitic iron ore reserves have remained largely unexploited. The dephosphorization of high phosphorus iron ore has been researched in many countries, such as physical separation, [6][7][8][9][10] bio-leaching, 11,12) flotation, 13,14) hydrometallurgical process. 15,16) But the oolitic structure of the ore prevents the effective use of physical concentration and flotation separation, and necessitates the use of chemical leaching.…”
Section: Introductionmentioning
confidence: 99%